1984
DOI: 10.1128/jb.158.2.701-704.1984
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant density variation during the cell cycle of Saccharomyces cerevisiae

Abstract: Cell buoyant densities of the budding yeast Saccharomyces cerevisiae were determined for rapidly growing asynchronous and synchronous cultures by equilibrium sedimentation in Percoll gradients. The average cell density in exponentially growing cultures was 1.1126 g/ml, with a range of density variation of 0.010 g/ml. Densities were highest for cells with buds about one-fourth the diameter of their mother cells and lowest when bud diameters were about the same as their mother cells. In synchronous cultures inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 8 publications
3
32
1
Order By: Relevance
“…In our model, the resultant affinity (  only varies slightly with the culture conditions, which can be regarded as reasonable (Kubitschek et al, 1983;Kubitschek et al, 1984;Baldwin and Kubitschek, 1984). In addition, other studies in several experimental situations supported the influence of biomass on substrate affinity (Contois, 1959;Roques, 1982).…”
Section: Discussionsupporting
confidence: 61%
“…In our model, the resultant affinity (  only varies slightly with the culture conditions, which can be regarded as reasonable (Kubitschek et al, 1983;Kubitschek et al, 1984;Baldwin and Kubitschek, 1984). In addition, other studies in several experimental situations supported the influence of biomass on substrate affinity (Contois, 1959;Roques, 1982).…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, when relating cAMP to dry mass a high level is observed during G 1 and a significant decrease before the cells start budding. As the variation in cell density is quite low at high growth rates (<1% wet weight) (Baldwin and Kubitschek, 1984) due to small changes in storage carbohydrate content (Silljé et al , 1997), cell dry mass can be assumed to correlate fairly well with cell volume. Thus, the intracellular cAMP concentration can indeed be expected to decline before S phase begins, possibly relieving the PKA‐mediated repression of CLN1 and CLN2 transcription (Baroni et al , 1994; Tokiwa et al , 1994).…”
Section: Resultsmentioning
confidence: 99%
“…A convenient estimate of mean cellular volume for modelling purposes can be obtained by measuring cell dry weight (DW) in asynchronous cultures (Theobald et al , 1997; Vaseghi et al , 2001) where the population distribution is fairly constant, and thus also the mean cell density. However, this is no longer true when analysing synchronous cultures because the cell density is known to fluctuate during the cell cycle (Hartwell, 1970; Baldwin and Kubitschek, 1984). Here the cell density varies mainly due to periodic accumulation and breakdown of trehalose and glycogen, which is especially pronounced at low growth rates (Woldringh et al , 1993; Duboc, 1996; Silljé et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the size, density can also explain the Intec Red profile. Thus, Baldwin et al (23) indicated that yeast cells suffer a variation of the density during the cell cycle and cells with small buds showed the highest values. The lowest density was found when bud diameter coincided with the mother cell diameter.…”
Section: Correlation Of Wine Fermentation Activity Of Yeasts Inocula mentioning
confidence: 99%